Interplay between miRNA regulation and mechanical stress for CUC gene expression at the shoot apical meristem - Fal, Kateryna (Plant Signal Behav, 2015)
The shoot apical meristem is the central organizer of plant aerial organogenesis. The molecular bases of its functions involve several cross-talks between transcription factors, hormones and microRNAs. We recently showed that the expression of the homeobox transcription factor STM is induced by mechanical perturbations, adding another layer of complexity to this regulation. Here we provide additional evidence that mechanical perturbations impact the promoter activity of CUC3, an important regulator of boundary formation at the shoot meristem. Interestingly, we did not detect such an effect for CUC1. This suggests that the robustness of expression patterns and developmental programs is controlled via a combined action of molecular factors as well as mechanical cues in the shoot apical meristem.